Protective effects of irbesartan on apoptosis in experimental diabetic nephropathy - Tunçdemir, Matem; Öztürk, Melek (Cerrahpaşa Medical Journal, 2014)
Objectives: The aim of this study is to investigate effects of irbesartan as an Ang II type 1 blocker on apoptosis and anti-apoptotic protein Bcl-2 in the streptozotocin (STZ)-induced diabetic rat. Methods: 24 male Wistar albino rats were used for three groups. The first group was the non-diabetic control group. Second group was the untreated STZ-induced diabetic group, (60 mg/kg, single dose, i.p). The third group was irbesartan treated (15 mg/kg/day, intragastric, for 4 week) STZ-diabetic rats. During the period of the experiment, blood glucose and microalbuminuria levels of the rats were measured. At the end of the study renal tissue samples were fixed in neutral formalin and embedded in paraffin. Tissue sections were examined for apoptosis by TUNEL method and for anti-apoptotic protein Bcl-2 by immunohistochemical staining. Results: The microalbuminuria levels of the irbesartan treated diabetic group were found reduced when compared with the untreated diabetic group (p<0,001). Widespread apoptosis was seen in the tubules of untreated diabetic group (p<0,01) and a decrease in the immunoreactivity of Bcl-2 were observed in glomeruli of the diabetic group. In the irbesartan treated diabetic group, antiapoptotic Bcl-2 immunoreactivity was similar to the results obtained from the control group and a decrease the number of apoptotic cells were observed. Conclusion: The results suggested that irbesartan treatment has renoprotective effects in STZ-diabetic nephropathy. AT1 receptor blockade inhibites Ang II mediated apoptosis in the STZ-diabetic nephropathy.